Analysis of Right Issue Announcement Effect toward Stock Price Movement and Stock Trading Volume within Issuer in Indonesia Stock Exchange - Wilson Yaputra Yakup; Yoyo Cahyadi (Binus Business Review, 2016)
The purpose of this study were to identify and analyze the rights issue effect to the stock price, the effect of the rights issue on stock trading volume, the correlation between stock prices before and after the right issue, as well as the correlation between volume of trading activity before the right issue and after that event. The objects of the study are the companies listed on Indonesia Stock Exchange (JSX). The hypothesis stated that right issues have a significant effect on stock price on companies listed on the JSX, rights issues have a significant effect on the stock trading volume on companies listed on the JSX, there is a significant correlation between stock price before and after the rights issue on companies listed in JSX, there is a significant correlation between volume of the stock trading before the rights issue and after that event. Data analysis used were descriptive statistics, simple linear regression analysis and paired t-test. Hypothesis testing was performed by using the Pearson correlation test with significance level of 5%. The results show that the right issue has a positive effect but not significant toward stock prices of companies listed in JSX, right issue has a negative effect and not significant toward the trading volume activity (TVA) on companies listed in JSX.